Is histopathological examination necessary after sacrococcygeal pilonidal sinus excision - ERGENÇ, MUHAMMER (My University, 2023)
Background: Pilonidal sinus is a common disease that usually occurs in the natal cleft in the sacrococcygeal region. Many conservative and surgical methods are used in its treatment. Malignancy is rarely detected in pilonidal sinus specimens; therefore, the routine pathological examination is controversial. In the literature, studies suggest histopathological evaluation if risk factors such as atypical presentation and appearance, older age, long-term disease, and recurrent disease are present. This study aimed to evaluate the pathology results of patients who underwent sacrococcygeal pilonidal sinus excision in our clinic.Methods: The records of patients admitted to Istanbul Sultanbeyli State Hospital and who underwent pilonidal sinus excision between January 2016 and October 2021 were reviewed retrospectively. The following parameters were evaluated: age, gender, location of disease, and histopathological examination result of pilonidal sinus specimens.Results: During the study, 2091 patients underwent surgery for pilonidal sinus disease in our general surgery clinic. The data of 2068 patients were analyzed after excluding 23 patients who underwent excision for disease outside the sacrococcygeal region and had missing data. The ages of the patients ranged from 13 to 72, with a female/male ratio of 535/1533. The mean age was 24.7 ± 8.2 years. Pilonidal sinus specimen pathologies excised from the sacrococcygeal region were examined. No malignancy was detected in any patient.Conclusion: Routine histopathological examination of pilonidal sinus specimens may be unnecessary if there are no risk factors such as atypical presentation and appearance, relapse, long-term disease, and advanced age.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Genel Cerrahi; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; General Surgery; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; Cerrahi; Surgery; Pilonidal sinus; Pilonidal sinus disease; Sacrococcygeal pilonidal sinus; Pathology